2017
DOI: 10.3201/eid2311.170833
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis ofKlebsiella pneumoniaefrom Hospitalized Children, Pakistan

Abstract: Klebsiella pneumoniae shows increasing emergence of multidrug-resistant lineages, including strains resistant to all available antimicrobial drugs. We conducted whole-genome sequencing of 178 highly drug-resistant isolates from a tertiary hospital in Lahore, Pakistan. Phylogenetic analyses to place these isolates into global context demonstrate the expansion of multiple independent lineages, including K. quasipneumoniae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 12 publications
1
46
2
Order By: Relevance
“…For OmpK35, premature stop codons were detected in 772 (29%) gene products (Table S1). These terminating mutations are found throughout the phylogeny but were enriched in the dominant lineage of K. pneumoniae CC258 and strains from a recent survey of a major hospital in Pakistan (42) (Fig. 1A).…”
Section: Resultsmentioning
confidence: 95%
“…For OmpK35, premature stop codons were detected in 772 (29%) gene products (Table S1). These terminating mutations are found throughout the phylogeny but were enriched in the dominant lineage of K. pneumoniae CC258 and strains from a recent survey of a major hospital in Pakistan (42) (Fig. 1A).…”
Section: Resultsmentioning
confidence: 95%
“…The dominance of four globally important clones (STs: 15; 101; 307; 874) amongst the K. pneumoniae at CUH (41%) (Additional file 1: Figure S3A; Additional file 2: Table S1) was led by ST15 which is strongly linked to outbreaks in hospitals [8,17,18]. ST101 has been highlighted for its association with extensive resistance and KPC carbapenemases [19], and ST307 was reported in a recent large-scale analysis of carbapenem-resistant isolates [20,21].…”
Section: K Pneumoniae and Enterobacter Represented Flowing Vs Staticmentioning
confidence: 99%
“…similipneumoniae (previously KPIIB), K. variicola (previously KPIII) [5], as well as two strains forming divergent lineages indicating potentially novel species within this species complex [6]. Whole genome sequencing (WGS) has shown that the predominant cause of clinical infection worldwide has been K. pneumoniae (KpI) [5] but there is an increasing trend, and increasing concern, in the detection of severe cases due to the newly described species [7]. Different studies report K. quasipneumoniae isolates causing infections resistant to treatments with ceftazidime and other oxyimino-betalactam antibiotics, and widespread carriage of genes encoding carbapenemase (KPC) [3,4,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%